US Interest in Military Intervention in Libya - Rakhmadi, Roby (Terekam Jejak Publisher, 2025)
This study aims to determine the national interests of the United States in NATO's Military Intervention in Libya in 2011. This study uses a qualitative descriptive method. The results of the study show that America has political motives in the event. The conclusion of the study is that in the intervention, although there has been a change of leadership in NATO, the US still plays an important role in the war. By involving other countries through multilateralism efforts, America can achieve its interests while sharing the burden borne in the war.